Stanovení kotininu v moči jako objektivní ukazatel kouření cigaret u nemocných s chronickým onemocněním ledvin - Jones-Burton, C; Vessal, G; Brown, J; Dowling, T. C; Fink, J. C (Postgraduální nefrologie, 2007)
Smoking is a modifiable behaviour that may hasten the progression of chronic kidney disease (CKD). Cotinine, a nicotine metabolite, is measurable in body fluids, including urine, and can be utilized as an objective measure of smoking exposure. Its use has not been examined in the CKD population. METHODS: In this cross-sectional study, we evaluated use of 24-h urinary cotinine excretion (Ucot) as a quantitative index of smoking exposure in a CKD population. Methods of comparison included self-report and expired air carbon monoxide (eCO) as standard measures of smoking exposure. Assessments of kidney function included estimated glomerular filtration rate (eGFR) and 24-h urinary protein (Uprot) excretion. RESULTS: Sixty-one patients were enrolled, of whom 12 were excluded for incomplete urine collections. Of the remaining, 77% were active current smokers (mean cigarettes smoked: 12+/-7 per day). The mean eGFR was 47+/-25 ml/min/1.73 m2 with no significant differences among non-smokers. The mean eCO and Ucot were significantly higher in smokers vs non-smokers (12.5+/-6.9 ppm and 1.3+/-1.1 ppm and 1685.87+/-922.77 microg/d and 134.18+/-445.03 microg/d, respectively, P<0.001 for both). Ucot was weakly correlated with eGFR (R=0.40, P=0.005), but not with Uprot (R=0.09, P=0.54). In multivariate analyses, daily cigarette consumption and eCO were the only significant predictors of Ucot (P<0.05 for both). CONCLUSION: In this CKD cohort, Ucot is correlated with commonly used measures of smoking exposure and is minimally influenced by underlying renal function, demonstrating its potential utility in clinical trials examining change in smoking behaviour and effects on renal injury.
Keywords: kouření; hodnoty glomerulární filtrace; chronická nemoc; ženské pohlaví; Surveys and Questionnaires; Smoking; lidé; multivariační analýza; Kidney Diseases; senioři; Cohort Studies; Aged; Cotinine; Chronic Disease; lidé středního věku; Circadian Rhythm; Humans; průzkumy a dotazníky; cirkadiánní rytmus; průřezové studie; Multivariate Analysis; nemoci ledvin; mužské pohlaví; Cross-Sectional Studies; kotinin; Male; Breath Tests; dechové testy; Middle Aged; Glomerular Filtration Rate; kohortové studie; Female